PENGARUH MOTIVASI KERJA DAN ETOS KERJA TERHADAP KINERJA KARYAWAN PADA PT. INDOMARCO PRISMATAMA CABANG PARUNG - Endang Susilo Wardani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to examine the effect of work motivation and work ethic on employee performance at PT. Indomarco Prismatama, Parung Branch. The research employs a quantitative research method with a survey approach. The sample consists of 65 respondents who are employees of PT. Indomarco Prismatama, Parung Branch. The data analysis techniques used include simple linear regression, multiple linear regression, correlation coefficient analysis, coefficient of determination, partial testing (t-test), and simultaneous testing (F-test). The results indicate that, partially, work motivation has a positive and significant effect on employee performance, as evidenced by a t-value greater than the t-table value (7.375 > 1.998) and a significance level of 0.000 < 0.05. Likewise, work ethic partially has a positive and significant effect on employee performance, as shown by a t-value greater than the t-table value (8.863 > 1.998) and a significance level of 0.000 < 0.05. Simultaneously, work motivation and work ethic have a significant effect on employee performance, which is proven by an F-value greater than the F-table value (47.583 > 3.15) and a significance level of 0.000 < 0.05. Therefore, it can be concluded that improving work motivation and work ethic simultaneously contributes significantly to enhancing employee performance at PT. Indomarco Prismatama, Parung Branch.